Physical activity as a modifiable risk factor for periodontal disease - Chan, Charlotte Cheuk Kwan; Chan, Alice Kit Ying; Chu, Chun Hung; Tsang, Yiu Cheung (Frontiers in Oral Health, 2023)
Non-communicable diseases (NCDs), which contribute significantly to global morbidity, are largely preventable through behavioral changes. As with other NCDs, periodontitis is associated with modifiable risk factors such as smoking and stress and is linked to multiple adverse health outcomes through a shared pathway of chronic systemic inflammation. While the health benefits of physical activity have been widely promoted in public health and extensively studied for other systemic conditions, its impact on periodontal health has only recently started to gain attention. This article critically evaluates the current literature on the relationship between physical activity and periodontitis. While cross-sectional studies have shown an inverse association between physical activity levels and periodontitis risk in the general population, clinical oral health surveys of elite athletes with high levels of physical activity have nonetheless revealed periodontal problemspoor periodontal conditions. have nonetheless been identified in elite athletes with high levels of physical activity. Although causality has not been determined, physical activity could positively impact periodontitis directly, by reducing inflammatory biomarkers, and indirectly, through its modulatory effects on insulin sensitivity, body massobesity, bone density, and stress, and other health promoting behaviors. However, confounding factors, differences in measurements and non-standardized variables to quantify activity levels present challenges in comparing studies. Given the importance of risk factor control during initial periodontal therapy, understanding the role of physical activity as a potential behavioral risk modifier is paramount. The findings of this review provide an evidence-based overview of how physical activity could influence periodontitis. There is a need for longitudinal cohort studies to verify the temporality of the reported associations and exclude confounders, while interventions are needed to assess the efficacy of physical activity on periodontal treatment outcomes.